COMPLICATIONS CAUSED BY IRON DEFICIEN ANEMIA DURING PREGNANCY AND THE IMPORTANCE OF CLINICAL-LABORATORY DIAGNOSIS (CIPEEX, 2024)
ANEMIA IS DEFINED ACCORDING TO HEMOGLOBIN LEVELS, WHICH CAN VARY ACCORDING TO MANY FACTORS,MAINLY AGE, SEX AND ETHNICITY. THE IMPACTS OF ANEMIA DURING PREGNANCY INVOLVE NEGATIVEEFFECTS ON MATERNAL HEALTH THAT CAN LEAD TO DEATH AND DEATH ON FETUSES. LABORATORY EVALUATIONIS ESSENTIAL FOR THE DEFINITIVE DIAGNOSIS OF IRON DEFICIENCY AND EARLY TREATMENT. THE STUDY AIMSTO DESCRIBE THE IMPACTS OF MATERNAL ANEMIA AND IRON DEFICIENCY DURING PREGNANCY, AS WELL ASTHE CLINICAL AND LABORATORY DIAGNOSIS OF THE PATHOLOGY. THIS IS A NARRATIVE REVIEW OF THELITERATURE. SCIENTIFIC ARTICLES WILL BE ANALYZED ON GOOGLE SCHOLAR AND IN THE DATABASESPUBMED, SCIELO (SCIENTIFIC ELECTRONIC LIBRARY ONLINE), MEDLINE (NATIONAL LIBRARY OFMEDICINE) PUBLISHED BETWEEN 2018 AND 2023, SELECTED FROM THE TITLES THAT CONTAIN REFERENCESTO THE DESCRIPTORS. RESEARCH HAS SHOWN THAT IT IS IMPORTANT TO HAVE AN ADEQUATE BALANCE OFBODY IRON FOR WELL-BEING AND QUALITY OF LIFE. IN PREGNANT WOMEN, IT IS NECESSARY TO HAVE GOODIRON LEVELS FOR A GOOD OUTCOME OF THE PREGNANCY, FOR THE MOTHER'S WELL-BEING AND FOR THENORMAL DEVELOPMENT OF THE FETUS AND MATURITY OF THE NEWBORN. ORAL IRON SUPPLEMENTATION ISTHE FIRST LINE OF TREATMENT IN CASES OF MILD ANEMIA, HOWEVER, CONSIDERING THE NUMEROUSGASTROINTESTINAL SIDE EFFECTS THAT OFTEN LEAD TO POOR ADHERENCE, OTHER THERAPEUTIC STRATEGIESSHOULD BE EVALUATED. MORE EFFORTS MUST BE DEVOTED BY THE PRENATAL HEALTHCARE SYSTEM TOERADICATE THIS SIGNIFICANT PROBLEM, AS CHILDREN BORN TO IRON-DEFICIENT MOTHERS ARE SUSCEPTIBLETO VARIOUS HEALTH PROBLEMS.
Keywords: Iron deficiency anemia; Pregnancy; Prenatal